2013
DOI: 10.5194/asr-10-65-2013
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic benefits of weather and climate services in Europe

Abstract: Abstract. There is a rising interest around the world for a better understanding of the economic and social value added of weather services. National hydro-meteorological services and international cooperative bodies in meteorology have ever more to justify their use of public budgets. Furthermore, the development of hydrological and meteorological services is to a large extent steered by expectations regarding the eventual benefits of the envisaged new developments. This article provides a compact overview of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Given the competition for scarce public funds (e.g. Rogers and Tsirkunov, 2013;Perrels et al, 2013), estimates of the economic value can help providers justify funding and guide priorities to invest in managing the impacts of weather and climate across economic sectors. A clear understanding of the value associated with climate services can help providers of the services to tailor the services to further maximize the value obtained from their use (Zillman, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Given the competition for scarce public funds (e.g. Rogers and Tsirkunov, 2013;Perrels et al, 2013), estimates of the economic value can help providers justify funding and guide priorities to invest in managing the impacts of weather and climate across economic sectors. A clear understanding of the value associated with climate services can help providers of the services to tailor the services to further maximize the value obtained from their use (Zillman, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We found that that there have been significant efforts to understand the value of the information. Mutiple studies summarized the literature, including case studies, and methods of valuation of hydro-meteorological systems and meteorological information [16][17][18][19][20]. In addition, there was a number of empirical studies focused on different sectors (agriculture, residential, energy, health, multiple sectors or all sectors).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nygård [30] estimated the costs of the Finnish marine monitoring program and used cost-benefit analysis to assess the value of environmental monitoring. [16] Hydrometeorological systems Multiple users/sectors Worldwide Literature review Leviäkangas [17] Meteorological information N/A Literature review Frei [10] Meteorology and climatology information Household, Ag, and energy Switzerland A case study using benefit transfer Anaman and Lellyett [8] Weather [18] Meteorological services N/A Worldwide Literature review Park et al [9] Meteorological services Household Korea Contingent valuation Kenkel and Norris [11] Real-time mesoscale weather information Agriculture Oklahoma Contingent valuation Frei et al [25] Meteorological services Transportation Switzerland Surveys Perrels et al [19] Weather and climate services N/A Europe Literature review Von Gruenigen et al [26] Meteorological services Transportation/aviation Switzerland The avoided cost Rogers and Tsirkunov [20] Early warning system N/A Worldwide Literature review Lazo et al [5] Weather forecasts Household U.S. Contingent valuation Kite-Powell [27] Physical Oceanographic Real-Time System Navigation Houston/Galveston, U.S.…”
Section: The Direct Market Approachmentioning
confidence: 99%
“…In this context, valuation studies can be helpful in understanding the value and benefits of using weather and climate information (such as SCF) to support decision‐making processes. Other areas such as, climate services (Adams, Eitland, Vaughan, & Wilby, ; Anderson et al, ; Clements, Ray, & Anderson, ; Ferguson, Finucane, Keener, & Owen, ; Perrels, Frei, Espejo, & Jamin, ), meteorological services (Frei & von, ; Hallegatte, ; Perrels et al, ; Pilli‐Sihvola, Namgyal, & Dorji, ), humanitarian response (Drechsler & Soer, ; Rodrigues et al, ; Stephens, Perez, Kruczkiewics, Boyd, & Suarez, ; World Food Programme, ) and disaster risk reduction and management (Hallegatte, ; Practical Action, ) have all highlighted the need for such valuations and the pursuit for this type of studies can be underpinned by a number of reasons, including (adapted from Anderson et al, ; Clements et al, ; Freebairn & Zillman, ): Justify publicly expenditure in the provision of climate information and services. This is particularly relevant in the context of public services, such as those provided by the National Meteorological and Hydrological Services (NMHS), where it is frequently argued the importance of ascertaining the benefits and services provided by NMHS and demonstrate how it supported better decision‐making and policy development in order to justify and secure sustained public investment.…”
Section: Introductionmentioning
confidence: 99%